The Study of Phase Behavior of Multi-Component Alkane–Flue Gas Systems Under High-Temperature Conditions Based on Molecular Dynamics Simulations - Xiaokun Zhang; Jiagao Tang; Zongyao Qi; Suo Liu; Changfeng Xi; Fang Zhao; Ping Hu; Hongyun Zhou; Chao Wang; Bojun Wang (Energies)
Injecting industrial high-temperature flue gas into hydrocarbon reservoirs has emerged as a novel approach for carbon sequestration. However, the complex high-temperature phase behavior between flue gas (CO2, N2) and reservoir fluids challenges this technology’s development, as traditional experimental methods and theoretical models often fall short in capturing it accurately. To address this, molecular dynamics simulations were employed in this study to investigate the phase behavior of single-component alkanes, multicomponent alkane mixtures, and multicomponent alkane–flue gas systems under high-temperature conditions. The results reveal that CO2 can become miscible with alkanes, while N2 diffuses into the system, causing volumetric expansion and a reduction in density. The initially distinct phase interface between the multicomponent alkanes and the flue gas becomes progressively blurred and eventually disappears, indicating the formation of a fully miscible phase. Comparative simulations revealed that the diffusion coefficients of N2 and CO2 increased by up to 20% with rising temperature and pressure, while variations in flue gas composition had negligible effects, indicating that high-temperature and high-pressure conditions significantly enhance flue gas–alkane miscibility.